Landslide dams induced by typhoon morakot and risk assesment - Chen, Su-Chien; Hsu, Chung-Li; Hu, Tingyeh; Chou, Hsien-Ter; Cui, Peng (Italian journal of engineering geology and environment, 2011)
<span data-sheets-value="{"1":2,"2":"As with other compound disasters caused by climate change, the occurrence probabilities of landslide dams and their secondary disasters have increased and became a serious issue after the 2009 Morakot typhoon in Taiwan. This paper describes the mechanism of the landslide dam formation. Different types of landslide dams are classi ed by their danger level. This study also describes the inducements behind earthquake- landslide-triggered and typhoon-triggered landslide dams and compared their differences. Finally, both engineering and non-engineering aspects of the disaster management strategies are outlined. This study concluded that better disaster management strategies for landslide dams should focus on the long-term mitigation which includes a warning and monitoring system, engineering facilities, and a response process."}" data-sheets-userformat="{"2":13057,"3":{"1":0},"11":0,"12":0,"15":"Arial","16":10}">As with other compound disasters caused by climate change, the occurrence probabilities of landslide dams and their secondary disasters have increased and became a serious issue after the 2009 Morakot typhoon in Taiwan. This paper describes the mechanism of the landslide dam formation. Different types of landslide dams are classi ed by their danger level. This study also describes the inducements behind earthquake- landslide-triggered and typhoon-triggered landslide dams and compared their differences. Finally, both engineering and non-engineering aspects of the disaster management strategies are outlined. This study concluded that better disaster management strategies for landslide dams should focus on the long-term mitigation which includes a warning and monitoring system, engineering facilities, and a response process.